Jurisdição constitucional e a tutela dos direitos metaindividuais - Akaoui, Fernando Reverendo Vidal (2009)
The present thesis try to demonstrate on a esquematic way that the constitutionals principles and rules should be always considerad as a diffuse or collective rights or interests, while abstractively arranged on our legal system, it doesn t matter if its exercices be individualy realized. Also, that any attempt to the Federal and States Constitutions, through the edition of normative acts that with then are incompatible, traslate a true offense to those, because of its transindividual and indivible charactistics. It does the distinction between primary and secondary diffuses and collective rights and interests, where the first ones would be just those that are disposed on a abstractive way on the Federal and States Constitutions, and give the necessary support to the entire national legal system; the secondary, on a different way, are those concretely specified on the diversity of sub-constitutional normative acts, and, even though, should have a collective protection, are resulting of the solid base criated by the primary, which give then the foundation. Also tries to demonstrate, that the unique importance that envolves the concentrate control of constitutionality, which has the nature of a collective action, this roll of legitimateds still not suficient to give the necessary guaranty to our society, specialy because of the political positions that commonly are taken by those who are listed as capable to it. On our vision, the federative principle is extremely weacked by the moment that the institution which the Constitutition entrust the deffense of the legal order and the democracy it self, the Public Attorney Offices, is represented, on the concentrate constitutional control actions, only by the Chief of the Federal Public Attorney, as if he has any kind of hierarchy or ascendancy to the State Attorney General Offices. Because of that, if now a days the Governor of a State or the Representatives of the States Deputies do not process the capable actions to correct a offensive act to a constitutional right, the State Attorney General Office can t do it, just having the right to claim to the Federal Attorney General, witch can or canot embrace the thesis. It is necessary to change the Constitution, to put on the roll of legitimated to iniciate a concentrate control of constitutionality action, the States Attorneys Generals, to pay homage to the federative principle, and on respect to the States population